Radiolabeling and quality control of therapeutic radiopharmaceuticals: optimization, clinical implementation and comparison of radio-TLC/HPLC analysis, demonstrated by [177Lu]Lu-PSMA - Eline L. Hooijman; Carolline M. Ntihabose; Thom G. A. Reuvers; Julie Nonnekens; Else A. Aalbersberg; Jordy R. J. P. van de Merbel; Judith E. Huijmans; Stijn L. W. Koolen; Jeroen J. M. A. Hendrikx; Erik de Blois (SpringerOpen, 2022)
Abstract Background Radiopharmaceuticals are considered as regular medicinal products and therefore the same regulations as for non-radioactive medicinal products apply. However, specific aspects should be considered due to the radiochemical properties. Radiopharmaceutical dedicated monographs are developed in the European Pharmacopoeia to address this. Currently, different quality control methods for non-registered radiopharmaceuticals are utilized, often focusing on radio-TLC only, which has its limitations. When the radiochemical yield (RCY) is measured by radio-TLC analysis, degradation products caused by radiolysis are frequently not detected. In contrast, HPLC analysis defines the radiochemical purity (RCP), allowing for detection of peak formation related to radiolysis. During the introduction and optimization phase of therapeutic radiopharmaceuticals, significant percentages of impurities, like radiolysed construct formation, may have consequential impact on patient treatment. Since more hospitals and institutes are offering radiopharmaceutical therapies, such as [177Lu]Lu-PSMA with an in-house production, the demand for adequate quality control is increasing. Here we show the optimization and implementation of a therapeutic radiopharmaceutical, including the comparison of ITLC and HPLC quality control. Results Downscaled conditions (74 MBq/μg) were in concordance to clinical conditions (18 GBq/250 µg, 5 mL syringe/100 mL flacon); all results were consistent with an > 98% RCY (radio-TLC) and stability of > 95% RCP (HPLC). Radio-TLC did not identify radiolysis peaks, while clear identification was performed by HPLC analysis. Decreasing the RCP with 50%, reduced the cell-binding capacity with 27%. Conclusion This research underlines the importance of the radiolabeling and optimization including clinical implementation and clarifies the need for cross-validation of the RCY and RCP for quality control measurements. Only HPLC analysis is suitable for identification of radiolysis. Here we have proven that radiolysed [177Lu]Lu-PSMA has less binding affinity and thus likely will influence treatment efficacy. HPLC analysis is therefore essential to include in at least the validation phase of radiopharmaceutical implementation to ensure clinical treatment quality.